Translation and Validation of Autism Spectrum Screening Questionnaire in Urdu for Autistic Children - Hijab Saeed, Shoaib Waqas, Muhammad Tariq, Hafiz Muhammad Asim, Maleeha Fuad (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: The objective of this study is Translation and validation of autism spectrum screening questionnaires in Urdu. Methods: This was a cross-cultural validation study conducted at the Rising Sun Institute in Lahore utilizing convenient sampling. Twenty pediatric rehabilitation experts and parents of children with autism spectrum disorders, ranging in age from 6 to 17, were included in the study. Two different translators translated the original English edition of ASSQ into Urdu (forward translation). One of the translators was a technological expert, while the other was a medical professional. These interpreters could communicate well in both English and Urdu. The Urdu version of the ASSQ was subsequently translated into English (backward translation). This was carried out by a healthcare expert who had been blinded to the original English version of the ASSQ. The final version was given to an expert panel for assessment after both scales were compared. Panel created the final translated Urdu version of the data. The guardian’s approval was obtained in advance, and anonymity was guaranteed. The data was entered into and analyzed using the SPSS version 21 application. The variables in the study were represented using descriptive statistics such as tables, graphs, and percentages. Results: For reliability statistics, the mean age of the participants was 54.87, with a standard deviation of 0.7648. The translated ASSQ questionnaire had a Cronbach’s alpha of 0.584. After testing and re-testing on parents of Autism patients, the inter item correlation (Pearson Correlation) varied between (0.510-0.845). After translation of ASSQ, the intra-class correlation varied from 0.345 to 0.484. Conclusion: Urdu version of autism spectrum screening questionnaire is a valid and reliable tool for autism children.